DIGITAL STORYTELLING UNTUK MENGEMBANGKAN ASPEK SPIRITUAL ANAK TAMAN KANAK-KANAK (TK) AL-HIDAYAH BAKUNG 01 KABUPATEN BLITAR - Nila Zaimatus Septiana (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2018)
This research endeavor to examine effectiveness of Digital Storytelling technique to develop kindergarten students’ spirituality aspect. Spirituality is mental dimension that make someone think about life meaning, value, believe, someone’s relations with God-with other humans-and the universe. Literally, someone’s spirituality can’t be measured, but it manifest in behavior shape can. This research is an experiment research with digital storytelling technique developed by Lambert, Weinshenker and others in Centre of Digital Storytelling (CDS). Digital storytelling is a technique that combined traditional understanding from a story with different type using digital multimedia. This technique expecting development of childrens’ spirituality level. Research method used in this research is within group or individual design and the research design using equivalent time series with researchers’ modification.